The role of governance in reforming the Palestinian water and sanitation sector - Rammal, Fuad Yousef; Alkhazzan, Bouchta (Journal of Humanities & Social Sciences, 2022)
The research objective has identified the role of governance in the reform of the water and sanitation sector, and the research problem was identified in determining the concerns of the deterioration of the role of governance in reforming the Palestinian water and sanitation sector due to the political, financial and organizational challenges facing the sector. During the governance interventions that were approved in the National Water Policy in Palestine 2013-2032, in the West Bank and Gaza Strip in Palestine, a basic hypothesis was developed that revolved around that the role of governance in reforming the water and sanitation sector is moving forward in accomplishing what was planned according to measure the impact of governance in the reform process and to match the percentages of achievement with what has been planned, and took the analytical approach and used the focusing group "Delphi policies" as a tool to analyze data collected by reviewing reports, records, plans and policies, as well as different related literature, making temporal and quantitative comparison of numbers and indicators contained in approved surveys. The research concluded with several results groups, most importantly the weak role of governance in the reform of the Palestinian water and sanitation sector, which appeared in two groups, the first related to the domination of the Israeli occupation on the hydro geo- politics on the West Bank and Gaza Strip, the second group of reasons related to organizational errors in the structural and institutional formation in the Palestinian water sector. The research recommended to work on building an advanced information system, activates the role of commitment, accountability, cooperation, and partnership, and reactivate the establishment of a national water company, regional water utilities and water user associations. Furthermore, it recommended changing the leadership of the center to the decentralized level and the development and adoption of an organizational structure of the water authority that coincide with its assigned role in the management of Palestinian water and sanitation sector.